The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/ejm-08-2015-0595
|View full text |Cite
|
Sign up to set email alerts
|

Just doing it: theorising integrated marketing communications (IMC) practices

Abstract: European Journal of Marketing1 Abstract Purpose While Integrated Marketing Communication (IMC) is a well-known concept in academia, there is insufficient theorisation on what it means 'to do' IMC in practice. Despite broad acceptance for IMC, there has been scant application of available organisational and sociological theories to illuminate actual IMC practices in the field. Drawing from the 'Practice Turn' in management studies, this paper elaborates on the concept of 'IMC practice' and provides an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
(117 reference statements)
0
23
0
Order By: Relevance
“…Also, the results of the study rhymed within the results of Ots & Nyilasy (2017) who argued that IMC can be activated mostly through the communication medium of the social media in which the organization can have a direct communication line with the customers in order to guarantee the retention of the current customers and the attracting of the potential customers.…”
Section: Resultsmentioning
confidence: 55%
“…Also, the results of the study rhymed within the results of Ots & Nyilasy (2017) who argued that IMC can be activated mostly through the communication medium of the social media in which the organization can have a direct communication line with the customers in order to guarantee the retention of the current customers and the attracting of the potential customers.…”
Section: Resultsmentioning
confidence: 55%
“…Our study responds to calls for more exploratory research in advertising (Belk 2017;Goulding 2017;Faber 2015), contributes a new, deep ethnographic perspective to the practiceturn in advertising (Ots and Nyilasy 2017) and contributes to the practice-turn in management studies more broadly (Schatzki 1996(Schatzki , 2002(Schatzki , 2012Skålén and Hackley 2011). Following Schatzki (2002) and Ots and Nyilasy (2017) the study found that each of the three sets of social practices deployed routines, material set-ups, rules and procedural knowledge, cultural templates and teleoaffective structures in different ways. The five elements of practices that Ots and Nyilasy (2017) found around the IMC process were broadly supported in the study, although the specific manifestations were different.…”
Section: Discussionmentioning
confidence: 79%
“…Following Schatzki (2002) and Ots and Nyilasy (2017) the study found that each of the three sets of social practices deployed routines, material set-ups, rules and procedural knowledge, cultural templates and teleoaffective structures in different ways. The five elements of practices that Ots and Nyilasy (2017) found around the IMC process were broadly supported in the study, although the specific manifestations were different. For example, routines were evident where experienced practitioners referred to the Persuasive Power they had learned to wield, for example where the agency presented three creative pathways to clients, where they 'made clients tired' by presenting huge volumes of finished work, by the selectively presented use of statistical research data, and where 'Becky' deployed the team support approach.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Schultz et al's (2014, p. 455) aspirational claim that 'IMC can be recast as the base for rethinking and replacing traditional marketing theory' is in stark contrast to Cornelissen's (2001Cornelissen's ( , 2003 and Ots and Nyilasy' (2017) criticisms that IMC is falsely presented as a panacea for marketing and lacks rigorous theorisation. Though the marketing literature continues to stress the need for further study to empirically unpack the organisational role of IMC, IMC implementation remains under researched.…”
Section: Introductionmentioning
confidence: 99%